Peningkatan Kemampuan Keluarga di Masyarakat dalam Merawat Anggota Keluarga Pasca Stroke dengan screening Gula Darah dan Kolesterol, Latihan Pasif Otot (ROM) dan Edukasi Diet di Puskesmas Alai Padang - Netti; Yosi Suryarinilsih (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2023)
Stroke patients often experience weakness on one side of the body or both with varying muscle strength values. Stroke patients, apart from experiencing weakness in part or both extremities, will also experience emotional instability. The aim of this activity is to determine the ability of families in the community to care for family members after stroke by screening blood sugar and cholesterol, passive muscle training (ROM) and diet education at the Alai Padang Community Health Center. This activity is carried out through community gathering methods, identifying risk factors, counseling and providing training to the community. The results of the activity showed that people at the Nanggalo Padang Community Health Center had the highest risk factors for stroke, namely 55% (n: systole > 120 and diastole > 80 mmHg). Those who wanted to check themselves to check their peripheral blood were 13 people. Those with high cholesterol were 76.9%, while those with high blood sugar values were 7.6%, with the highest age of the community being 70 years and the youngest being 33 years. The conclusion of this activity is increased public understanding of how to reduce risk factors for stroke.